Der Briefwechsel zwischen August Sauer und Bernhard Seuffert 1880 bis 1926 Auswahl und Kommentar - Fetz, Bernhard (2019)
With more than 1200 letters the correspondence between August Sauer (1855-1926) and Bernhard Seuffert (1853-1938) is one of the most comprehensive scholarly correspondences of the late 19th and the early 20th century. Their work had a huge impact on the development of the subject "Neuere deutsche Literaturgeschichte". The main goal of the project is the presentation of a selection of letters, combined with rich annotations as well as registers for persons and works.